Extracellular Fragmented Self-DNA Is Involved in Plant Responses to Biotic Stress - Barbero, Francesca; Guglielmotto, Michela; Islam, Monirul; Maffei, Massimo E. (Frontiers in Plant Science, 2021)
A growing body of evidence indicates that extracellular fragmented self-DNA (eDNA), by acting as a signaling molecule, triggers inhibitory effects on conspecific plants and functions as a damage-associated molecular pattern (DAMP). To evaluate early and late events in DAMP-dependent responses to eDNA, we extracted, fragmented and applied the tomato (Solanum lycopersicum) eDNA to tomato leaves. Non sonicated, intact self-DNA (intact DNA) was used as control. Early event analyses included the evaluation of plasma transmembrane potentials (Vm), cytosolic calcium variations (Ca2+cyt), the activity and subcellular localization of both voltage-gated and ligand-gated rectified K+ channels and the reactive oxygen species (ROS) subcellular localization and quantification. Late events included RNA-Seq transcriptomic analysis and qPCR validation of gene expression of tomato leaves exposed to tomato eDNA. Application of eDNA induced a concentration-dependent Vm depolarization which was correlated to an increase in (Ca2+)cyt; this event was associated to the opening of K+ channels, with particular action on ligand-gated rectified K+ channels. Both eDNA-dependent (Ca2+)cyt and K+ increases were correlated to ROS production. In contrast, application of intact DNA produced no effects. The plant response to eDNA was the modulation of the expression of genes involved in plant-biotic interactions including pathogenesis-related proteins (PRP), calcium-dependent protein kinases (CPK1), heat shock transcription factors (Hsf), heat shock proteins (Hsp), receptor-like protein kinases (RLK) and ethylene-responsive factors (ERF). Several genes involved in calcium signaling, ROS scavenging and ion homeostasis were also modulated by application of eDNA. Shared elements among the transcriptional response to eDNA and to biotic stress indicate that eDNA might be a common DAMP that triggers plant responses to pathogens and herbivores, particularly to those that intensive plant cell disruption or cell death. Our results suggest the intriguing hypothesis that some of the plant reactions to pathogens and herbivores might be due to DNA degradation, especially when associated to the plant cell disruption. Fragmented DNA would then become an important and powerful elicitor able to trigger early and late responses to biotic stress.